The academic misconduct as a sinful Islamic behaviour in an academia - Che Omar, Azman (Universiti Teknologi MARA, Kelantan, 2018)
Academic misconduct is not a new issue of integrity in academia. There were claims and proofs that plagiarism as the main type of academic misconduct that are committed by university students is rampant and pervasive at most of the higher institutional learning and education. Plagiarism is a sinful behavior in an academia. Alas, to prove that it is in existence is not difficult. One can look at the many student projects and by checking the literature review, any research course lecturer can pinpoint the places or areas that seem not to be done by the students themselves. Indirectly, they copy from someone else. Plagiarism as for an issue is the lack of integrity inside the student’s moral obligation. In embracing the ethics of writing, one should not take from someone without giving or citing the original writer as the owner of the ideas or writings. Any student should know that the sentences that they are writing whether it is coming from them or they took from others. If it is not from them, in many instances they need to cite it. If not, by using it, they are having mala fide intention and this thing should be avoided at all. For Muslim persons, they are accountable of their works to the Al-Mighty Allah in the Hereafter. The purpose of this paper is to study the attitudinal and behavior of university students towards plagiarism activity. An empirical study of consisting 150 bachelor degree students was conducted at a branch of an established public university. The research methods used were quantitative, survey using self-administered questionnaires and deductive approach. The findings of the research show that the factors that make the students plagiarised are the accessibility of the internet, lack of awareness and the pressure of completing the assignment and not the personal values and attitude of the students. Several items concerning the attitudes and behavior of the students using Pearson correlation and multiple regression analysis that were analysed have confirmed that the students did commit the plagiarism activity. The strategies and the activities that should be taken by lecturers and the university respectively are further recommended for managing the plagiarism.